Sistem Pendukung Keputusan Penilaian Kinerja Tenaga Honorer Menerapkan Metode Weighted Product (WP) dan Complex Proportional Assessment (COPRAS) dengan Kombinasi Pembobotan Rank Order Centroid (ROC) - Yarimani Laia; Mesran Mesran; I Gede Iwan Sudipa; Darma Setiawan Putra; Perani Rosyani; Riska Aryanti (PDSI, 2023)
Honorary workers are someone who is appointed by a Personnel Development Officer or other officials in the government to carry out certain tasks in government agencies whose salary is paid by the APBN or APBD. The performance evaluation of honorary workers is aimed at planning the development of human resources and training and increasing the utilization of honorary workers in accordance with their duties and functions. The process of assessing the performance of honorary workers who are unfair can have an adverse effect on the honorary workers themselves. In the process of evaluating honorary staff, an efficient system is needed to see the performance results of the honorary staff, a Decision Support System is needed. The method applied in this study is the Weighted Product (WP) and Complex Proportional Assessment (COPRAS) methods applying Rank Order Centroid (ROC) weighting using these two methods, it is expected to provide effective results in evaluating honorary workers. The final results obtained in calculating the best alternative value in the calculation of the Weighted Product (WP) method, namely A4 on behalf of